Q. Serenus, Liber medicinalis 3-4 - Michael Reeve (Exemplaria Classica, 2009)
Possible instances of hiatus in Serenus's hexameters are examined and the one transmitted at v. 4 rejected in favour of a forgotten conjecture by the elder Burman.